Pengembangan Video Pembelajaran Menggunakan AVS Video Editor pada Materi Peradaban Bangsa Arab Pelajaran Sejarah Kebudayaan Islam Kelas X MA Al Fattahiyyah - Ella Dwiyanti Zulfa; Fahrur Rozi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The This study aims to develop an instructional video using the AVS Video Editor application on the topic of Arab Civilization in the Islamic Cultural History subject for Grade X students at MA Al Fattahiyyah. The background of this research is based on the need for engaging and interactive learning media to improve students’ understanding of historical content.The research employs a Research and Development (R&D) method using the ADDIE development model, which consists of five stages: Analyze, Design, Develop, Implement, and Evaluate. Data collection techniques include questionnaires, observations, and documentation. Questionnaires were distributed to media and content experts to assess the quality and feasibility of the video, and to students to gather their responses to the developed media. Observations were carried out to examine student engagement during the learning process, while documentation was used to collect supporting evidence throughout the development process.The results show that the instructional video developed in this research is considered